A promising biomarker adaptive Phase 2/3 design – Explained and expanded - Cong Chen; Linda Sun; Xuekui Zhang (Contemporary Clinical Trials Communications, 2023)
This short communication concerns a biomarker adaptive Phase 2/3 design for new oncology drugs with an uncertain biomarker effect. Depending on the outcome of an interim analysis for adaptive decision, a Phase 2 study that starts in a biomarker enriched subpopulation may continue to the end without expansion to Phase 3, expand to Phase 3 in the same population or expand to Phase 3 in a broader population. Each path can enjoy full alpha for hypothesis testing without inflating the overall Type I error.